A techno-feminist analysis of beauty app development in China's high-tech industry. - Peng, Altman Yuzhu (Journal of Gender Studies, 2021)
Drawing on a techno-feminist approach, this article foregrounds the socio-technological process of beauty app development in China's high-tech industry. I conducted semi-structured interviews with ten professionals, six women and four men, who previously worked at a leading Chinese high-tech company and participated in the development of a pioneer, popular beauty app – BeautyCam (Meiyan Xiangji). The research findings reveal that Chinese high-tech professionals often perceive the development of beauty apps as providing female users with a sense of empowerment and facilitating the inclusion of female professionals in the high-tech industry. Despite this feminist veneer, beauty app development poses no challenge to the status quo in Chinese society. Instead, it supports an underlying gendered logic not only by reinforcing existing standards of beauty but also in creating a niche job market that restricts female professionals' career development. The discussion sheds light on the intersection of gender and technology in an East Asian context where neoliberal pseudo-feminism is evidently on the rise.